’’Narodovlastije’ as the end of democracy? (Some thoughts about "new" Russian rhetoric) - Lassan, Eleonora; Makarova, Viktorija (Respectus Philologicus, 2004)
The present paper sets out to investigate the possibility of judging the speaker’s ideological convictions referring to certain word usage. The act of engaging the words being used into certain interdiscourse allows to activate the ideological field in which one or another signifier acquires corresponding ideological connotations and it is related to other signifiers of the same ideological field by the means of associations. Moreover, semantically identical words but different in origin tend to belong to different ideological fields. The analysis of separate word usage in the texts of the President of Russia and the party in power affords a possibility to speak about the change in political directions of the country. However, the changes are not presented explicitly.